2020
DOI: 10.1111/jocn.15593
|View full text |Cite
|
Sign up to set email alerts
|

Embedded researchers in Australia: Survey of profile and experience across medical, nursing and midwifery and allied health disciplines

Abstract: To support the implementation of research evidence into practice, the embedded researcher model, where a researcher is embedded as a core member of the clinical team, offers promise. The aim of this study was to investigate and compare how the embedded researcher model has been adopted by different professional discipline groups in Australia. A purposive sample of current and former embedded researchers were invited to participate in an exploratory online survey. Responses were described using Excel and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, pharmacy residency projects that had co‐investigators affiliated with a university and a high h‐index were also shown to increase the rates of publications 19 . Similar benefits on departmental research culture have also been observed in medical, nursing, and allied health professional departments 20,21 . On the other hand, only half of the articles identified had at least one author with a hospital pharmacy department affiliation only.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, pharmacy residency projects that had co‐investigators affiliated with a university and a high h‐index were also shown to increase the rates of publications 19 . Similar benefits on departmental research culture have also been observed in medical, nursing, and allied health professional departments 20,21 . On the other hand, only half of the articles identified had at least one author with a hospital pharmacy department affiliation only.…”
Section: Discussionmentioning
confidence: 70%
“…19 Similar benefits on departmental research culture have also been observed in medical, nursing, and allied health professional departments. 20,21 On the other hand, only half of the articles identified had at least one author with a hospital pharmacy department affiliation only. This means the authors with joint university and hospital affiliations may not be regularly involving pharmacists from their pharmacy department in their research.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that this can occur through strategic investment in partnerships between academic institutions and health care providers, with financial investment in the creation of new research development initiatives ( Paterson and Strickland, 2023 ) which has been successful in other professions ( Borges et al., 2010 ). The benefits for health systems that incorporate nursing clinician researcher roles are being realised ( Wu et al., 2018 ; Krishmasamy and Chan, 2016 ; Australian Clinical Trials Alliance and Quantium Health Outcomes, 2017 ; Misso et al., 2016 ; Blevins and Millen, 2016 ), despite the historical professional and structural barriers ( Newington et al., 2020 ; Barton-Burke, 2016 ; Mickan et al., 2017 ; Mickan and Coates, 2022 ; Carthon et al., 2017 ; Middlebrooks et al., 2016 ; Black et al., 2019 ; Eckert et al., 2022 ; Duff et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aligning with the purpose of this work, this review defines research education and training programs as organised initiatives or interventions that are either discrete (e.g., standalone workshops or research days) or longer in their duration (e.g., research courses or a series of workshops or lectures) wherein curriculum is developed and shared with multiple individuals or participants, with a view to develop and apply research skills [2,5]. Healthcare settings are considered those wherein the provision of healthcare is considered core business (e.g., hospitals, community-based health services, cancer care services, family medicine clinics) and is therefore the setting in which research evidence needs to be applied or translated to reduce the gap between research knowledge and practice [2,20].…”
Section: Introductionmentioning
confidence: 99%